Nepotistic Hiring and Poverty From Cultural, Social Class, and Situational Perspectives - Jain, Luke; Gál, Éva; Orosz, Gábor (Frontiers in Psychology, 2022)
Being poor can influence how one makes ethical decisions in various fields. Nepotism is one such area, emerging as kinship-based favoritism in the job market. People can be poor on at least three levels: one can live in a poor country (cross-cultural poverty), be poor compared to others around them (socio-economic poverty), or feel poor in their given situation (situational poverty). We assumed that these levels can influence simultaneously nepotistic hiring decisions among Hungarian (N=191) and US participants (N=176). Prior cross-cultural studies demonstrated that nepotism is more prevalent in poorer countries such as Hungary than in richer countries such as the USA. However, contrary to our expectations, US participants showed stronger nepotistic behavioral tendencies than Hungarians (cross-cultural level). Furthermore, independently from the culture, people with lower socioeconomic status had less nepotistic intentions than richer people (socio-economic level). When participants were asked to imagine themselves as a poor person (situational level), they tended to be more nepotistic than had they imagined themselves to be rich. Finally, nepotistic hiring intentions were in general stronger than non-nepotistic hiring intentions. These paradoxical results are interpreted in the light of the cultural differences between the COVID-19 job market contexts and explained by the simultaneous presence of the risk aversion and mechanisms revealed by research on wealth and immoral behaviors.